2 Statutes at Large of Pennsylvania from 1682 to 1801 420 (1896) - (:unkn) unknown (My University, 1712)
"And that no master or commander of any merchant ship or vessel shall fire, or suffer to be fired, on board his vessel, any ordnance or other gun after eight o'clock in the evening, nor before daylight in the morning, without license from the governor first had, under the penalty of ten shillings for every of fense. Nor shall any person presume to fire any gun, guns or small arms within the built part of the said city, without special license from the governor, or some magistrate of the said city for so doing, under the penalty of two shillings and six pence for every offense."
Keywords: DISCHARGE (LIKELY OF CANNON) FROM SHIPS AND DISCHARGES IN TOWN. THE TERM "GUN" IN THIS PERIOD OFTEN MEANS CANNON, NOT SMALL ARMS.